Assessment of self-medication practice for oral health problems among people of Varanasi, Uttar-Pradesh, India - Dubey, Pragati; Mittal, Neelam (International Journal Of Community Medicine And Public Health, 2022)
Background: Self medication has been practiced for centuries in both industrialized and under developed countries. There are lots of literatures indicating people awareness regarding abuse of medicines and antibiotics without a doctor’s prescription, but there has not been much study conducted for dental illness. The present study aimed to gather information about self-medication pattern among people of Varanasi, Uttar-Pradesh and to identify the measures to curb these life-threatening practices. Methods: An observational based cross-sectional study was carried out in OPD of Faculty of Dental Sciences, IMS, BHU, Varanasi. The sample size comprised of 500 respondents. The SPS software was used to code, input, and analyze all descriptive data. Descriptive data analysis was performed and the results were provided as frequencies and percentage. Results: The response of survey received a perfect score of 100%. The prevalence rate of self medication was found to be 56.2%. The main reason for engaging in such life threatening practice was lack of time and ignorance. Analgesia was the most commonly utilized type of medication. Out of 281, 84 patients sought basic care from a pharmacist, whereas 49.2% patient approached to visit dentist only when their problem continued. Conclusions: The prevalence rate was higher in male than female. Controlling self-medication requires patient health awareness initiatives, community pharmacist help, and pharmacist continuing education. There is a need for intervention planning to encourage rational self-medication through mass media such as newspapers, magazines and TV.